Corticotropin-Releasing Factor and Toll-Like Receptor Gene Expression Is Associated with Low-Grade Inflammation in Irritable Bowel Syndrome Patients with Depression - Song Jizhong; Wang Qiaomin; Wang Chao; Li Yanqing (Gastroenterology Research and Practice)
The mechanism of low-grade inflammation in irritable bowel syndrome (IBS) is unclear; our research concentrates on the involvement of the corticotropin-releasing factor (CRF) and Toll-like receptor (TLR) gene expression in the process of low-grade inflammation in IBS patients with depression. This study suggests more IBS patients are presenting with the states of depression and anxiety. IBS patients with depression have shown a lower grade inflammatory response and an imbalance of the inflammatory response. CRF1, CRF2, TLR2, and TLR4 in IBS patients with depression are significantly higher than those without depression and controls. Thus, activation of the CRF-TLR associated pathways produces an inflammatory reaction, which can concurrently affect the digestive tract and the CNS and induce the corresponding digestive and psychiatric symptoms.